On the spectroscopy of bremsstrahlungs produced by an electron accelerator - Tran , Duc Thiep; Truong , Thi An; Phan , Viet Cuong; Nguyen , The Vinh; Nguyen , Tuan Khai (Nuclear Science and Technology, 2013)
Although electron accelerators are equipments which accelerate electron, in fact they are intense sources of bremsstrahlung photon and neutron beams. Therefore the study on spectroscopy of bremsstrahlung is of great importance. This work presents the results obtained by the authors about the energy distribution of bremsstrahlung spectra, the method for determination of bremsstrahlung photon flux as well as the possibilities for producing neutron and neutron rich radioactive ions beams for fundamental research and practical applications.